OPTIMALISASI PENGAWASAN ORANG ASING OLEH KANTOR IMIGRASI DALAM MENJAGA STABILITAS KEAMANAN NASIONAL - Muna Imtinan Maitsa; Imma Yedida Ardi; Mas Budi Priyatno (STKIP Subang, 2026)
Supervision of foreigners and their activities within Indonesian territory is an important part of maintaining national security stability. The development of globalization and the increasing mobility of foreign nationals have had positive impacts on the economic, investment, and tourism sectors. However, it also creates potential immigration violations, particularly misuse of stay permits. This study aims to analyze the optimization of foreigner supervision by Immigration Offices in preventing the misuse of stay permits and maintaining national security stability. The research method used is normative legal research with statutory and conceptual approaches. Data were obtained through literature studies by reviewing laws and regulations, scientific journals, and other relevant legal sources. The results show that supervision of foreigners has been carried out through administrative and field supervision, but several obstacles remain, such as limited human resources, weak inter-agency coordination, and increasingly complex modes of stay permit violations. Therefore, optimization efforts are needed through strengthening digital supervision systems, increasing inter-agency synergy, and improving the capacity of immigration officers to enhance the effectiveness of foreigner supervision in Indonesia.